Turismo rural na Rota Colonial Linha Stein, Salvador do Sul/RS: incremento de renda e bem-estar para famílias e comunidade - Moraes, Cléia dos Santos (2006)
This research evaluate the level and composition of the budget , as well the welfare of the families who are part of the Linha Stein colonial route, and work with rural tourism, as well the neighboring families that doesn t work with rural tourism. To the evaluation was prepared an instrument to collect the data to survey the incomes and the pointers of welfare of the families. The used methodology contemplated the qualification of the families in agreement the activities that were developed by its members. The results show that the families who are part of the script, as well as that do not make part, are in its majority pluriactivity and its incomes are composed with priority for the agricultural income, being that the not-agriculturist income offers an important contribution. One also verified an important participation of the source retirements and pensions in income. About the welfare of the families, in all of them was found a high level. The profile of the tourists indicated for the entrepreneurs was, mainly, of people of third age that travel in groups searching for tranquility. The activity of rural tourism provided to the families an increment in the income and a good level of welfare. These had been extended, indirectly and some times directly to the families who do not work with rural tourism that are part of the community.